Adrenal function and microbial DNA in noninfected cirrhotic patients with ascites: Relationship and effect on survival. Issue 8 (August 2015) - Risso, Alessandro; Alessandria, Carlo; Mezzabotta, Lavinia; Elia, Chiara; Andrealli, Alida; Spandre, Maurizio; Di Luigi, Paola; Barbui, Anna; Evangelista, Andrea; Morgando, Anna; Serra, Roberto; Ciccone, Giovannino; et al.
Abstract Background There are few data on clinical relevance of adrenal dysfunction and its relationship with occult microbial DNA in noninfected haemodynamically stable cirrhotic patients with ascites. Aims The aim of this study was to evaluate prognostic role of adrenal dysfunction, microbial DNA, and their relationship. Methods Adrenal function was assessed in 93 consecutive patients following a corticotropin stimulation test. Adrenal dysfunction was defined as: basal cortisol <10 μg/dl, delta cortisol <9 μg/dl, or peak cortisol <18 μg/dl. Microbial DNA was assessed in blood and ascites of 54 consecutive patients. Patients were followed up until liver transplantation or death. Results Adrenal dysfunction was not significantly associated with mortality, while the risk of death rose significantly with an increase in basal cortisol values (HR 1.13 per 1-μl/dl increase; 95% CI 1.01–1.26). Microbial DNA was independently associated with reduced survival (HR 8.05, 95% CI 1.57–41.2). In microbial DNA-positive patients a significant correlation was found between Model for End-Stage Liver Disease (MELD) score and basal cortisol values (Pearson's r = 0.5107; p = 0.018). Conclusions Microbial DNA and MELD score, but not adrenal function, were the best independent predictors of mortality in noninfected cirrhotic patients with ascites. High serum cortisol levels may be a systemic reaction to microbial translocation, increasing in parallel with deterioration of liver function.